Analysis of genetic linkage of HIV from couples enrolled in the HIV prevention trials network 052 trial - Susan H. Eshleman (2018)
Background. The HIV Prevention Trials Network (HPTN) 052 trial demonstrated that early initiation of antiretroviral therapy (ART) reduces human immunodeficiency virus (HIV) transmission from HIV-infected adults (index participants) to their HIV-uninfected sexual partners. We analyzed HIV from 38 index-partner pairs and 80 unrelated index participants (controls) to assess the linkage of seroconversion events. Methods. Linkage was assessed using phylogenetic analysis of HIV pol sequences and Bayesian analysis of genetic distances between pol sequences from index-partner pairs and controls. Selected samples were also analyzed using next-generation sequencing (env region). Results. In 29 of the 38 (76.3%) cases analyzed, the index was the likely source of the partner's HIV infection (linked). In 7 cases (18.4%), the partner was most likely infected from a source other than the index participant (unlinked). In 2 cases (5.3%), linkage status could not be definitively established. Conclusions. Nearly one-fifth of the seroconversion events in HPTN 052 were unlinked. The association of early ART and reduced HIV transmission was stronger when the analysis included only linked events. This underscores the importance of assessing the genetic linkage of HIV seroconversion events in HIV prevention studies involving serodiscordant couples. © 2011 The Author.